2022
DOI: 10.3389/fcvm.2022.970438
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative features of carotid and coronary atherosclerotic plaque among men and women

Abstract: Cardiovascular diseases (CVDs), particularly ischemic heart disease (IHD) and stroke, present epidemiologically in a different way among sexes. The reasons of these sex-based differences should be delved into sex-specific cardiovascular (CV) risk factors and different mechanisms of atherosclerotic progression. Imaging techniques of both carotid and coronary atherosclerotic plaques represent a tool to demonstrate sex-related features which might be used to further and better assess CV risk of male and female po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…However, El Mahdiui et al previously demonstrated that women <55 years showed a faster regression of fibrous and non-calcified plaques compared to men, but this difference was not observed in women >55 years, perhaps due to the loss of the protective effects of estrogen [11] . Several protective effects of estrogen on the development and progression of atherosclerotic plaque have been suggested, including its effect on the physiology of the endothelial cells, smooth muscle cells of the arterial wall, cardiomyocytes, extracellular matrix deposition, inflammation, and coagulation [26] , [28] . Women in our study, who were mostly post-menopausal, displayed an unaltered plaque composition over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, El Mahdiui et al previously demonstrated that women <55 years showed a faster regression of fibrous and non-calcified plaques compared to men, but this difference was not observed in women >55 years, perhaps due to the loss of the protective effects of estrogen [11] . Several protective effects of estrogen on the development and progression of atherosclerotic plaque have been suggested, including its effect on the physiology of the endothelial cells, smooth muscle cells of the arterial wall, cardiomyocytes, extracellular matrix deposition, inflammation, and coagulation [26] , [28] . Women in our study, who were mostly post-menopausal, displayed an unaltered plaque composition over time.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13]. In contrast to invasive imaging methods, non-invasive imaging techniques for atherosclerotic plaque detection with undoubted advantages, such as noninvasiveness, precision, high spatiotemporal resolution, and low toxicity, have taken a chief place [14,15]. So far, the main non-invasive imaging approaches for patients include ultrasound, X-ray, CT, and magnetic resonance imaging (MRI), having different uses [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…An example of the coronary artery is shown in Figure 1a, while the IVUS acquisition device for the coronary vascular system is shown in Figure 1b. The diagnosis of CAD is frequently made by coronary CT angiography (CCTA), which enables non-invasive measurement of the arterial lumen's diameter and plaque localization [16][17][18][19][20]. However, radiologists presently manually assess the location and severity of the plaque(s) leading to the stenosis in CCTA pictures, which, in addition to being The diagnosis of CAD is frequently made by coronary CT angiography (CCTA), which enables non-invasive measurement of the arterial lumen's diameter and plaque localization [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of CAD is frequently made by coronary CT angiography (CCTA), which enables non-invasive measurement of the arterial lumen's diameter and plaque localization [16][17][18][19][20]. However, radiologists presently manually assess the location and severity of the plaque(s) leading to the stenosis in CCTA pictures, which, in addition to being The diagnosis of CAD is frequently made by coronary CT angiography (CCTA), which enables non-invasive measurement of the arterial lumen's diameter and plaque localization [16][17][18][19][20]. However, radiologists presently manually assess the location and severity of the plaque(s) leading to the stenosis in CCTA pictures, which, in addition to being costly and time-consuming, is also susceptible to mistake and inaccuracy [21].…”
Section: Introductionmentioning
confidence: 99%